Translation error clusters induced by aminoglycoside antibiotics - Ingo Wohlgemuth; Raffaella Garofalo; Ekaterina Samatova; Aybeg Nafiz Günenç; Christof Lenz; Henning Urlaub; Marina V. Rodnina (Nature Communications, 2021)
Aminoglycoside antibiotics target the ribosome and induce misreading, yet which translation errors induce bacterial cell death is unclear. Here authors use quantitative mass spectrometry and show that bactericidal aminoglycosides induce clusters of errors in full-length proteins in vivo with as many as four amino acid substitutions in a row.